ANALYSIS OF COPYRIGHT OF SILVERWARE MOTIVE DESIGN AT CELUK, SUKAWATI, GIANYAR, BALI - Lodra, Dr. I Nyoman (IJRDO- Journal of Educational Research, 2016)
The infringement as meant is the plagiarism of silver motif design which belong to foreign businessmen that brought local designers so the case to Denpasar court. The American entrepreneurs who has silver businesses in Baturening, Mambal, Badung, claimed that the design motifs used by local craftsmen silver in Celuk, Sukawati, Gianyar, Bali imitated the designs created by him. The local craftsmen create the designs through creative process by setilir of the Balinese values. The creation process resulting intellectual treasures with novelty is believed to be recognized and receive copyright. so the local designers can be freed from worrisome of working under fearsome that they will violate the copyright. The background of the creation process in obtaining the copyright can be formulated as follows: (1) how the process of creating silver motif design is able to obtain a copyright, (2) how the concept of creating Celuk silver motif design, (3) how the criteria of Celuk silver motif design related to Copyright. From the background of the the problems, this study has objectives: (1) knowing the process of creating Celuk silver motif design, (2) determining the concept of creating Celuk silver, and (3) determining the copyright criteria in designing Celuk silver motif. The research methodology used in this study is descriptive qualitative using iconology, ethnography, and cultural approach with the perspective of the Copyright Act.